Full-degradable ultraviolet barrier film material as well as preparation method and application thereof

By using polycaprolactone triol and isophorone diisocyanate as raw materials and adding chlorogenic acid as ultraviolet absorbers, a fully degraded ultraviolet barrier film material was prepared, which solved the problem of aging of traditional polyurethane materials under ultraviolet irradiation and lack of ultraviolet shielding performance, and achieved efficient ultraviolet barrier and material performance improvement.

CN119661796APending Publication Date: 2025-03-21JINAN UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411923362.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Traditional polyurethane materials tend to age and degrade and turn yellow under ultraviolet irradiation, and do not have ultraviolet shielding properties, resulting in a shorter shelf life of food.

Method used

Polycaprolactone triol and isophorone diisocyanate are used as raw materials, and chlorogenic acid is added as ultraviolet absorbers to form carbamate bonds to prepare a fully degraded ultraviolet barrier film material.

Benefits of technology

This material not only has UV resistance, but also improves tensile strength, elongation at break, antioxidant activity, thermal stability and melting temperature, but also can be fully degraded, solving the problem of non-renewable resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661796A_ABST
    Figure CN119661796A_ABST
Patent Text Reader

Abstract

The invention discloses a full-degradable ultraviolet barrier film material as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing polycaprolactone triol with isophorone diisocyanate, adding a catalyst and a solvent, heating and stirring to obtain a polyurethane prepolymer solution; and adding an ultraviolet absorbent into the polyurethane prepolymer solution, heating and stirring, removing bubbles and drying to obtain the full-degradable ultraviolet barrier film material. According to the method, chlorogenic acid is added in the process of preparing the film material by taking polycaprolactone triol and isophorone diisocyanate as raw materials, so that the prepared full-degradable ultraviolet barrier film material has an anti-ultraviolet effect; meanwhile, the tensile strength, the elongation at break, the antioxidant activity, the thermal stability, the melting temperature and other properties of the thin film material prepared only from the polycaprolactone triol and the isophorone diisocyanate can be improved; wide application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a fully degradable ultraviolet blocking film material, a preparation method thereof, and applications thereof. Background Art

[0002] With the development of the times, people have put forward higher requirements for the various properties of packaging films. Most traditional packaging materials can only provide general physical protection for food, but they have poor mechanical properties, are easy to age, and are difficult to degrade. Polyurethane materials are widely used in the packaging field by adjusting the ratio of soft and hard segments to achieve performance selection and optimization. However, general polyurethane materials are prone to aging, degradation and yellowing under ultraviolet radiation, which not only accelerates the aging of the film. In addition, traditional polyurethane materials do not have UV shielding properties. Ultraviolet rays can easily pass through the film directly to the surface of food, which will greatly shorten the shelf life of food. Therefore, the current research focuses on the development of a polyurethane film material with high-efficiency UV shielding properties to meet the diverse needs of different fields. Summary of the Invention

[0003] In order to overcome at least one of the technical problems existing in the prior art, the present invention provides a fully degradable UV blocking film material and a preparation method and application thereof.

[0004] The technical solutions of the present invention are as follows:

[0005] The present invention first provides a method for preparing a fully degradable UV-blocking film material, which comprises the following steps:

[0006] The polycaprolactone triol and isophorone diisocyanate are mixed, a catalyst and a solvent are added, and the mixture is heated and stirred to obtain a polyurethane prepolymer (denoted as PU) solution;

[0007] An ultraviolet absorber is added to a polyurethane prepolymer solution, and a fully degradable ultraviolet barrier film material is obtained after heating, stirring, removing bubbles and drying.

[0008] The present invention uses polycaprolactone triol and isophorone diisocyanate as raw materials, chemically combining them to form urethane bonds. The prepared polyurethane is a bio-based polyurethane material, which overcomes the problem of non-renewable resources and other problems brought about by traditional petroleum-based polyurethane materials. In particular, by adding a UV absorber and chemically combining it with the polyurethane prepolymer, the prepared fully degradable UV barrier film material has an anti-UV effect.

[0009] Preferably, the polycaprolactone triol used is polycaprolactone triol with a molecular weight of 1500 to 2500.

[0010] Most preferably, the polycaprolactone triol used is polycaprolactone triol with a molecular weight of 2000.

[0011] Preferably, the catalyst is dibutyltin dilaurate.

[0012] Preferably, the solvent is tetrahydrofuran.

[0013] Preferably, the ultraviolet absorber is chlorogenic acid powder (denoted as CA).

[0014] The phenolic hydroxyl groups in chlorogenic acid (CA) and the conjugated C=C structure in the composite material are both chromophores that can absorb ultraviolet light in the medium and long wave regions. The fully degradable UV-blocking film material obtained by combining chlorogenic acid as an UV absorber with a polyurethane prepolymer can reduce the damage of ultraviolet light to polyurethane molecules and improve the anti-UV performance of the fully degradable UV-blocking film material.

[0015] The inventors also found in their research that the fully degradable UV-blocking film material obtained by combining chlorogenic acid as a UV absorber with a polyurethane prepolymer has a higher tensile strength, or even significantly higher, than the film material prepared without adding chlorogenic acid.

[0016] The inventors also found in their research that the fully degradable UV-blocking film material obtained by combining chlorogenic acid as a UV absorber with a polyurethane prepolymer has a higher elongation at break than, or even significantly higher than, the film material prepared without adding chlorogenic acid.

[0017] The inventors also found in their research that the fully degradable UV-blocking film material obtained by combining chlorogenic acid as a UV absorber with a polyurethane prepolymer has good antioxidant activity compared to the film material prepared without adding chlorogenic acid.

[0018] The inventors also found in their research that the fully degradable UV-blocking film material obtained by combining chlorogenic acid as a UV absorber with a polyurethane prepolymer has a higher thermal stability, or even significantly higher, than the film material prepared without adding chlorogenic acid.

[0019] The inventors also found in their research that the melting temperature of the fully degradable UV-blocking film material obtained by combining chlorogenic acid as a UV absorber with a polyurethane prepolymer is significantly higher than that of the film material prepared without adding chlorogenic acid.

[0020] Preferably, the added amount of the ultraviolet absorber is 1-10% of the mass of the fully degradable ultraviolet blocking film material.

[0021] Further preferably, the added amount of the ultraviolet absorber is 4-6% of the mass of the fully degradable ultraviolet blocking film material.

[0022] Studies have shown that the amount of chlorogenic acid added in the present invention has an important influence on the performance of the prepared fully degradable UV barrier film material; in particular, the effect on the elongation at break and the melting temperature of the prepared fully degradable UV barrier film material is most prominent.

[0023] Studies have shown that the addition of chlorogenic acid does not necessarily increase or even significantly increase the elongation at break and melting temperature of the prepared fully degradable UV-blocking film material.

[0024] Studies have shown that the elongation at break of the fully degradable UV-blocking film material first decreases and then increases with the addition of chlorogenic acid; when 2% of chlorogenic acid is added, the elongation at break of the fully degradable UV-blocking film material prepared decreases, and only when more than 4% of chlorogenic acid is added can the elongation at break of the fully degradable UV-blocking film material be significantly or even substantially improved.

[0025] Studies have shown that the melting temperature of the fully degradable UV blocking film material first decreases and then increases with the addition of chlorogenic acid; when 2% of chlorogenic acid is added, the melting temperature of the fully degradable UV blocking film material prepared decreases, while the melting temperature of the fully degradable UV blocking film material prepared when 4% of chlorogenic acid is added is significantly improved; and, the melting temperature of the fully degradable UV blocking film material prepared when 4% of chlorogenic acid is added is also higher than that of the fully degradable UV blocking film material prepared when 6% of chlorogenic acid is added.

[0026] Preferably, the specific conditions for heating and stirring after adding the catalyst and solvent are: stirring the reaction at a temperature of 60-70° C. for 0.5-1.5 h, and the stirring speed is 1500-2500 r / min.

[0027] Most preferably, the specific conditions for heating and stirring after adding the catalyst and the solvent are: stirring the reaction at a temperature of 65° C. for 1 hour, and the stirring speed is 2000 r / min.

[0028] Preferably, the molar ratio of the hydroxyl groups in the polycaprolactone triol to the isocyanate bonds in the isophorone diisocyanate is 1:1.

[0029] Preferably, the specific conditions for heating and stirring after the ultraviolet absorber is added to the polyurethane prepolymer solution are: stirring and reacting at a temperature of 60-70° C. for 8-12 hours, and a stirring speed of 1500-2500 r / min.

[0030] Most preferably, the specific conditions for heating and stirring after the ultraviolet absorber is added to the polyurethane prepolymer solution are: stirring the reaction at a temperature of 65° C. for 9 hours and a stirring speed of 2000 r / min.

[0031] The present invention also provides an application of the fully degradable UV-blocking film material prepared by the above-mentioned preparation method in the field of food preservation.

[0032] Beneficial effects: The present invention provides a novel method for preparing a fully degradable UV-blocking film material; in the method, chlorogenic acid is added during the process of preparing the film material using polycaprolactone triol and isophorone diisocyanate as raw materials, so that the prepared fully degradable UV-blocking film material has an anti-UV effect; at the same time, the method can also improve the tensile strength, elongation at break, antioxidant activity, thermal stability, melting temperature and other properties of the film material prepared only using polycaprolactone triol and isophorone diisocyanate as raw materials; and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the apparent morphology of the fully degradable UV blocking film material of the present invention.

[0034] Figure 2 This is a diagram showing the mechanical properties of the fully degradable UV-blocking film material prepared by adding different amounts of chlorogenic acid in the present invention.

[0035] Figure 3 This is a bar graph showing the DPPH radical scavenging rate of the fully degradable UV-blocking film material prepared by implementing the present invention with different chlorogenic acid addition amounts.

[0036] Figure 4 This is the infrared spectrum of the fully degradable UV-blocking film material prepared by adding different amounts of chlorogenic acid in the present invention.

[0037] Figure 5 This is a DSC-TG curve diagram of the fully degradable UV-blocking film material prepared by implementing different chlorogenic acid addition amounts in the present invention.

[0038] Figure 6 This is a transmittance curve of the fully degradable UV-blocking film material prepared by adding different amounts of chlorogenic acid in the present invention. DETAILED DESCRIPTION

[0039] The present invention is further explained below with reference to specific examples, but the examples do not limit the present invention in any form.

[0040] Example 1 Preparation of polyurethane film material

[0041] 3 g of polycaprolactone triol (PCL, molecular weight 2000) and 0.555 g of isophorone diisocyanate were accurately weighed using an electronic analytical balance and poured into a round-bottom flask containing 2 mL of tetrahydrofuran. The mixture was placed in a constant temperature oil bath and stirred at room temperature until completely dissolved. 50 μL of dibutyltin dilaurate catalyst was then added dropwise to the solution. The mixture was reacted at 65° C. for 10 h with a stirring speed of 2000 r / min. During this period, 2 mL of tetrahydrofuran solvent was added to the solution every 3 hours. After the reaction was completed, the polyurethane film-forming solution was obtained.

[0042] The above film-forming liquid was cast on a polytetrafluoroethylene template by a tape casting method and placed at room temperature for 12 hours. After the solvent evaporated, the template was placed in a vacuum drying oven at a drying temperature of 65°C and dried for 10 hours to form a film, thereby obtaining a polyurethane film material, which was recorded as PU.

[0043] Example 2 Preparation of fully degradable UV-blocking film material

[0044] 2.96 g of polycaprolactone triol (PCL, molecular weight 2000) and 0.555 g of isophorone diisocyanate were accurately weighed using an electronic analytical balance and poured into a round-bottom flask containing 2 mL of tetrahydrofuran. The mixture was placed in a constant temperature oil bath and stirred at room temperature until completely dissolved. 50 μL of dibutyltin dilaurate catalyst was then added dropwise to the solution. The mixture was reacted in an oil bath at 65°C for 1 h with a stirring speed of 2000 r / min. After the reaction was completed, a polyurethane prepolymer solution was obtained.

[0045] Accurately weigh 0.0161 g of uniformly ground chlorogenic acid (98%) powder using an electronic analytical balance and add it to the polyurethane prepolymer solution. React in a 65°C oil bath for 9 hours with a stirring speed of 2000 r / min. During this period, 2 mL of tetrahydrofuran solvent is added to the solution every 3 hours. After the reaction is completed, the polyurethane-chlorogenic acid film-forming solution is obtained.

[0046] The above film-forming liquid was cast on a polytetrafluoroethylene template by a tape casting method and placed at room temperature for 12 hours. After the solvent evaporated, the template was placed in a vacuum drying oven at a drying temperature of 65°C and dried for 10 hours to form a film, thereby obtaining a fully degradable UV blocking film material, which was recorded as PU-CA-2.

[0047] Example 3 Preparation of fully degradable UV-blocking film material

[0048] 2.90 g of polycaprolactone triol (PCL, molecular weight 2000) and 0.555 g of isophorone diisocyanate were accurately weighed using an electronic analytical balance and poured into a round-bottom flask containing 2 mL of tetrahydrofuran. The mixture was placed in a constant temperature oil bath and stirred at room temperature until completely dissolved. 50 μL of dibutyltin dilaurate catalyst was then added dropwise to the above solution. The mixture was reacted in a 65°C oil bath at a stirring speed of 2000 r / min for 1 h. After the reaction was completed, a polyurethane prepolymer solution was obtained.

[0049] Accurately weigh 0.0322 g of uniformly ground chlorogenic acid (98%) powder using an electronic analytical balance and add it to the polyurethane prepolymer solution. React in a 65°C oil bath for 9 hours with a stirring speed of 2000 r / min. During this period, 2 mL of tetrahydrofuran solvent is added to the solution every 3 hours. After the reaction is completed, the polyurethane-chlorogenic acid film-forming solution is obtained.

[0050] The above film-forming liquid was cast on a polytetrafluoroethylene template by a tape casting method and placed at room temperature for 12 hours. After the solvent evaporated, the template was placed in a vacuum drying oven at a drying temperature of 65°C and dried for 10 hours to form a film, thereby obtaining a fully degradable UV blocking film material, which was recorded as PU-CA-4.

[0051] Example 4 Preparation of fully degradable UV-blocking film material

[0052] 2.84 g of polycaprolactone triol (PCL, molecular weight 2000) and 0.555 g of isophorone diisocyanate were accurately weighed using an electronic analytical balance and poured into a round-bottom flask containing 2 mL of tetrahydrofuran. The mixture was placed in a constant temperature oil bath and stirred at room temperature until completely dissolved. 50 μL of dibutyltin dilaurate catalyst was then added dropwise to the above solution. The mixture was reacted in a 65°C oil bath at a stirring speed of 2000 r / min for 1 h. After the reaction was completed, a polyurethane prepolymer solution was obtained.

[0053] Accurately weigh 0.0483 g of uniformly ground chlorogenic acid (98%) powder using an electronic analytical balance and add it to the polyurethane prepolymer solution. React in a 65°C oil bath for 9 hours with a stirring speed of 2000 rpm. During this period, add 2 mL of tetrahydrofuran solvent to the solution every 3 hours. After the reaction is complete, the polyurethane-chlorogenic acid film-forming solution is obtained.

[0054] The above film-forming liquid was cast on a polytetrafluoroethylene template by a tape casting method and placed at room temperature for 12 hours. After the solvent evaporated, the template was placed in a vacuum drying oven at a drying temperature of 65°C and dried for 10 hours to form a film, thereby obtaining a fully degradable UV blocking film material, which was recorded as PU-CA-6.

[0055] The performance tests were performed on PU, PU-CA-2, PU-CA-4 and PU-CA-6 obtained in Examples 1 to 4, respectively.

[0056]

Appearance Analysis

[0057] The results are as follows Figure 1 As shown, the text underneath the four composite films is clearly visible, demonstrating their excellent transparency and gloss. The chlorogenic acid-modified composite film exhibits an overall light yellow color. The transparency of the film is not significantly affected by increasing the chlorogenic acid content, demonstrating the good compatibility between chlorogenic acid and polyurethane.

[0058]

Physical and mechanical properties analysis

[0059] Four composite film samples, labeled PU, PU-CA-2, PU-CA-4, and PU-CA-6, were cut into 30 mm x 10 mm strips. The cut film samples were secured to a tensile fixture with an initial clamp spacing of 25 mm and a tensile rate of 10 mm / s. The instrument was activated, and the probe was slowly stretched until the film broke. The tensile strength, elongation at break, and elongation at break were recorded and calculated. Five parallel sets of tests were performed for each specification.

[0060]

[0061] Where: Ts is the tensile strength, MPa; Eab is the elongation at break, %; F is the maximum tension when the membrane spline breaks, N; S is the membrane thickness, mm; L is the initial length of the membrane, mm; ΔL is the total length of the membrane when it breaks, mm.

[0062] The results are as follows Figure 2 As shown in the results, when chlorogenic acid (CA) was introduced into the polyurethane (PU) system, the mechanical properties of the resulting polyurethane-chlorogenic acid (PU-CA) composite were significantly enhanced compared to the pure polyurethane. In particular, the addition of chlorogenic acid resulted in a significant improvement in the tensile strength of the composite, increasing from 3.49 MPa to 8.78 MPa.

[0063] In addition to the increase in tensile strength, the elongation at break of the PU-CA composite material showed a trend of first decreasing and then increasing with increasing CA content. However, as the chlorogenic acid content continued to increase, the elongation at break gradually increased, reaching as high as 402% when the chlorogenic acid content was added at 6%.

[0064]

DPPH free radical scavenging rate determination

[0065] A 0.1 mmol / L DPPH methanol solution was prepared. Membrane extracts with varying chlorogenic acid contents were reacted with the DPPH methanol solution in the dark for 30 minutes, followed by centrifugation. The absorbance of the supernatant was measured at 517 nm and defined as Ac. A blank control, Ac, was prepared by replacing the membrane extract with a DPPH solution containing deionized water. Ascorbic acid was used as a positive control. Each experiment was conducted in parallel with four other groups. The free radical scavenging rate was calculated using the following formula:

[0066]

[0067] Where: DPPH is the DPPH free radical scavenging rate, %; Ac is the absorbance of methanol solution; As is the absorbance of methanol and membrane sample solution.

[0068] The results are as follows Figure 3 As shown in the figure, the antioxidant properties of the membrane samples showed a significant enhancement trend with the gradual increase of chlorogenic acid content. In particular, when the CA addition amount reached 6%, the membrane sample showed a DPPH scavenging capacity of up to 85.17%, which was comparable to the positive control, fully demonstrating that the membrane sample had good antioxidant activity.

[0069] Study on the mechanism of action of polyurethane film and polyurethane-chlorogenic acid composite film with different chlorogenic acid addition amounts

[0070] 1) Fourier transform attenuated total reflection infrared spectroscopy

[0071] The dried and balanced membrane sample was cut into a size of 10 mm × 10 mm, and the membrane sample was fixed on a Fourier transform infrared spectrometer. The ATR accessory was used for testing to observe the changes in the microstructure of each group in the membrane.

[0072] The results are as follows Figure 4 As shown, 1730cm -1 The peak at 3350cm belongs to the stretching vibration of -C=O bond. -1 The peak at 2250 cm is usually attributed to the amide A band caused by the stretching of -NH in the urethane bond. -1 The stretching vibration peak near 1445cm disappeared after polymerization, which indicated that the reaction generated a carbamate structure and successfully synthesized polyurethane. However, compared with the unmodified polyurethane film (PU), the composite material with chlorogenic acid added had a -1 There is a C=C vibration peak from aromatic hydrocarbons, and the peak intensity increases with the increase of chlorogenic acid content, which proves that chlorogenic acid is successfully compounded into polyurethane.

[0073] 2) Differential Scanning Calorimetry-Thermogravimetry (DSC-TG) Simultaneous Thermal Analyzer

[0074] Accurately weigh 6-8 mg of sample and place it in an alumina crucible. Set the test conditions to a nitrogen atmosphere, a constant heating rate of 10°C / min, a temperature range of 30-600°C, a carrier gas rate of 50 mL / min, and an empty crucible as a blank control to obtain the DSC-TG curve.

[0075] TGA results are as follows Figure 5 All samples shown in (a) exhibit degradation at temperatures exceeding 250°C, which is generally consistent with the application range of fresh food films. Polyurethane elastomers exhibit two distinct thermal decomposition stages within the 250-440°C range: the first (301°C-332°C) due to thermal degradation of the polyurethane hard segment; the second (419°C-422°C) due to mass loss caused by the decomposition of the polyurethane soft segment. Because the hard segment is more susceptible to thermal decomposition than the soft segment, the thermal stability of polyurethane is primarily determined by the hard segment. With increasing CA content, the decomposition temperatures of the two segments of the film material increase overall, and the weight retention at 600°C also increases. Furthermore, at 600°C, PU-CA-6 exhibits minimal mass loss, indicating that the increase in CA content alters the PU crystal structure, resulting in improved thermal stability of the composite.

[0076] DSC results are as follows Figure 5 As shown in (b), after adding CA to the PU matrix, the melting temperature increases from 305°C to 326°C. When the CA content is 4%, the melting temperature reaches the maximum, but when the CA content is 6%, the melting temperature decreases slightly.

[0077] 3) Ultraviolet absorption spectrum measurement of composite film

[0078] The transmittance of the composite polyurethane film was measured using a UV-visible spectrophotometer, scanning within the wavelength range of 200 to 800 nm. By reducing the transmittance of the composite cling film, food can be protected from UV radiation, which can accelerate the deterioration of the packaged product.

[0079] The results are as follows Figure 6 As shown, the transmittance of the polyurethane film (PU) without CA begins to rise at 320nm, proving that pure polyurethane itself has no UV shielding properties. However, the PU-CA composite material exhibits 0% transmittance throughout the entire near-UV range (180-400nm). This means that the composite material effectively blocks all UV rays within this wavelength range, demonstrating excellent UV blocking capabilities.

Claims

1. A method for preparing a fully degradable UV-blocking film material, characterized in that: The following steps are included: The polycaprolactone triol and isophorone diisocyanate are mixed, a catalyst and a solvent are added, and the mixture is heated and stirred to obtain a polyurethane prepolymer solution; The ultraviolet absorber is added into the polyurethane prepolymer solution, and the fully degradable ultraviolet barrier film material is obtained after heating, stirring, removing bubbles and drying.

2. The method for preparing the fully degradable UV blocking film material according to claim 1, characterized in that: The polycaprolactone triol used is polycaprolactone triol with a molecular weight of 1500-2500.

3. The method for preparing the fully degradable UV blocking film material according to claim 1, characterized in that: The catalyst is dibutyltin dilaurate.

4. The method for preparing the fully degradable UV blocking film material according to claim 1, characterized in that: The solvent is tetrahydrofuran.

5. The method for preparing the fully degradable UV blocking film material according to claim 1, characterized in that: The ultraviolet absorber is chlorogenic acid powder.

6. The method for preparing the fully degradable UV blocking film material according to claim 1, characterized in that: The added amount of the ultraviolet absorber is 1-10% of the mass of the fully degradable ultraviolet barrier film material.

7. The method for preparing the fully degradable UV blocking film material according to claim 1, characterized in that: The specific conditions for heating and stirring after adding the catalyst and the solvent are: stirring the reaction at a temperature of 60 to 70° C. for 0.5 to 1.5 hours, and the stirring speed is 1500 to 2500 r / min.

8. The method for preparing the fully degradable UV blocking film material according to claim 1, characterized in that: The molar ratio of the hydroxyl group in the polycaprolactone triol to the isocyanate bond in the isophorone diisocyanate is 1:

1.

9. The method for preparing the fully degradable UV blocking film material according to claim 1, characterized in that: The specific conditions for heating and stirring after the ultraviolet absorber is added to the polyurethane prepolymer solution are: stirring the reaction at a temperature of 60 to 70° C. for 8 to 12 hours, and the stirring speed is 1500 to 2500 r / min.

10. Use of the fully degradable ultraviolet blocking film material prepared by the preparation method according to any one of claims 1 to 9 in the field of food preservation.

Citation Information

Patent Citations

  • Antibacterial cationic waterborne polyurethane resin and preparation method thereof

    CN108299614A

  • Water-based hyperbranched polyurethane sizing agent with ultraviolet resistance and preparation method thereof

    CN112359603A

  • High-viscosity antibacterial bio-based waterborne polyurethane emulsion as well as preparation method and application thereof

    CN119060286A

  • Ultraviolet absorber and skin external agent containing the same

    JP1996151319A

  • Composition for blocking ultraviolet comprising aromatic amino acid or phenolic polymer as effective component

    KR101963344B1